“By ones and twos and tens”: pedagogies of possibility for democratizing higher education - Amsler, Sarah (Taylor & Francis, 2014)
This paper concerns the relationship between teaching and political action both within and outside formal educational institutions. Its setting is the recent period following the 2010 Browne Review on the funding of higher education in England. Rather than speaking directly to debates around scholar-activism, about which much has already been written, I want to stretch the meanings of both teaching and activism to contextualise the contemporary politics of higher learning in relation to diverse histories and geographies of progressive education more generally. Taking this wider view suggests that some of the forms of knowledge which have characterised the university as a progressive institution are presently being produced in more politicised educational environments. Being receptive to these other modes of learning can not only expand scholarly thinking about how to reclaim intellectual life from the economy within universities, but stimulate the kind of imagination that we need for dreaming big about higher education as and for a practice of democratic life.